The SARS-CoV-2 B.1.618 variant slightly alters the spike RBD–ACE2 binding affinity and is an antibody escaping variant: a computational structural perspective. Issue 48 (9th September 2021) - Khan, Abbas; Gui, Jianjun; Ahmad, Waqar; Haq, Inamul; Shahid, Marukh; Khan, Awais Ahmed; Shah, Abdullah; Khan, Arsala; Ali, Liaqat; Anwar, Zeeshan; Safdar, Muhammad; Abubaker, Jehad; et al.
Abstract : This study explored the binding patterns of the wild type and B.1.618 variant using which revealed that the B.1.618 variant possess a stronger binding affinity for the host ACE2 and escape the neutralizing antibodies. Abstract : Continuing reports of new SARS-CoV-2 variants have caused worldwide concern and created a challenging situation for clinicians. The recently reported variant B.1.618, which possesses the E484K mutation specific to the receptor-binding domain (RBD), as well as two deletions of Tyr145 and His146 at the N-terminal binding domain (NTD) of the spike protein, must be studied in depth to devise new therapeutic options. Structural variants reported in the RBD and NTD may play essential roles in the increased pathogenicity of this SARS-CoV-2 new variant. We explored the binding differences and structural-dynamic features of the B.1.618 variant using structural and biomolecular simulation approaches. Our results revealed that the E484K mutation in the RBD slightly altered the binding affinity through affecting the hydrogen bonding network. We also observed that the flexibility of three important loops in the RBD required for binding was increased, which may improve the conformational optimization and consequently binding of the new variant. Furthermore, we found that deletions of Tyr145 and His146 at the NTD reduced the binding affinity of the monoclonal antibody (mAb) 4A8, and that the hydrogen bonding network was significantly affected consequently. This data show that the new B.1.618 variant is an antibody-escaping variant with slightly altered ACE2–RBD affinity. Moreover, we provide insights into the binding and structural-dynamics changes resulting from novel mutations in the RBD and NTD. Our results suggest the need for further in vitro and in vivo studies that will facilitate the development of possible therapies for new variants such as B.1.618.